Ascaris suum excretory/secretory products differentially modulate porcine dendritic cell subsets - Hamid, Benjamin; Ebner, Friederike; Bechtold, Lalita; Kundik, Arkadi; Rausch, Sebastian; Hartmann, Susanne (Frontiers in Immunology, 2022)
Helminths produce excretory/secretory products (E/S) which can modulate the immune responses of their hosts. Dendritic cells (DC) are essential for initiating the host T cell response and are thus potential targets for modulation by helminth E/S. Here we study immunomodulation of porcine peripheral blood DC subsets following ex vivo stimulation with E/S from Ascaris suum, a common helminth of pigs with considerable public health and economic importance. Our data showed that the relative frequencies of DC subsets in porcine blood differ, with plasmacytoid DC (pDC) being the most prominent in healthy 6-month-old pigs. pDC are an important cytokine source, and we found that A. suum E/S suppressed production of the type 1 cytokines IL-12p40 and TNF-α by this subset following toll-like receptor (TLR) ligation. In contrast, conventional DC (cDC) are more efficient antigen presenters, and the expression of CD80/86, costimulatory molecules essential for efficient antigen presentation, were modulated differentially by A. suum E/S between cDC subsets. CD80/86 expression by type 1 cDC (cDC1) following TLR ligation was greatly suppressed by the addition of A. suum E/S, while CD80/86 expression by type 2 cDC (cDC2) was upregulated by A. suum E/S. Further, we found that IFN-γ production by natural killer (NK) cells following IL-12 and IL-18 stimulation was suppressed by A. suum E/S. Finally, in the presence of E/S, IFN-γ production by CD4+ T cells co-cultured with autologous blood-derived DC was significantly impaired. Together, these data provide a coherent picture regarding the regulation of type 1 responses by A. suum E/S. Responsiveness of pDC and cDC1 to microbial ligands is reduced in the presence of E/S, effector functions of Th1 cells are impaired, and cytokine-driven IFN-γ release by NK cells is limited.